Sub-acute oral toxicity of Hamo NK hard capsule in experimentalanimals - Phạm, Thủy Phương; Trịnh, Vũ Lâm; Phạm, Quốc Bình (Tạp chí Y Dược cổ truyền Việt Nam, 2023)
Background: Hamo NK hard capsule is composed of some dry extracts formulation of herbal medicine which had shown good properties effective treating dyslipidemia. However, there are no scientific reports of its toxicological properties which guarantee of the safety its usage as a potent treating dyslipidemia. Therefore, the present study was to investigate sub-acute toxicity of Hamo NK on rats through oral administration. Methods: The sub-acute administration Hamo NK was studied on Wistar rats. The animals were orally exposed to 0.25g/kg and 0.75 g/kg b.w/day of Hamo NK for 12 consecutive weeks. Physical observations and body weight were made during the study period. At the end of the experiment, blood samples were collected for hematology and clinical chemistry evaluations. Gross pathology and histopathology of livers and kidneys were assessed. Result: No major alteration was observed in the evaluated parameters at two doses of 0.25 g/kg per day and 0.75 g/kg per day. The histopathologic analysis of the livers and kidneys indicated architecture with normal aspect. Conclusion: Collectively, these data demonstrate that Hamo NK hard capsule has a high margin of safety.